More than a Metric: How Training Load is Used in Elite Sport for Athlete Management - West, Stephen W.; Clubb, Jo; Torres-Ronda, Lorena; Howells, Daniel; Leng, Edward; Vescovi, Jason D.; Carmody, Sean; Posthumus, Michael; Dalen-Lorentsen, Torstein; Windt, Johann (International Journal of Sports Medicine, 2020)
Training load monitoring is a core aspect of modern-day sport science practice. Collecting, cleaning, analysing, interpreting, and disseminating load data is usually undertaken with a view to improve player performance and/or manage injury risk. To target these outcomes, practitioners attempt to optimise load at different stages throughout the training process, like adjusting individual sessions, planning day-to-day, periodising the season, and managing athletes with a long-term view. With greater investment in training load monitoring comes greater expectations, as stakeholders count on practitioners to transform data into informed, meaningful decisions. In this editorial we highlight how training load monitoring has many potential applications and cannot be simply reduced to one metric and/or calculation. With experience across a variety of sporting backgrounds, this editorial details the challenges and contextual factors that must be considered when interpreting such data. It further demonstrates the need for those working with athletes to develop strong communication channels with all stakeholders in the decision-making process. Importantly, this editorial highlights the complexity associated with using training load for managing injury risk and explores the potential for framing training load with a performance and training progression mindset.
Keywords: workload; performance; injury; training